Pengaruh Pendapatan Sektor Perikanan Dan PertanianTerhadapPerekonomian Daerah Di Provinsi Lampung - Diana, Nora (Jurnal Ekonomika : INDEPENDEN, 2023)
The fisheries and agriculture sector in Lampung Province is the sector that received investment funds of 39.23%, which is greater than the industrial sector at 18.17%. In addition, the fisheries sector is the sector that has the top five income in the regional economy of Lampung province. However, the distribution, farmer exchange rate (NTP), and income of this sector have continued to decline in the last five years. This study aims to analyze the effect of fisheries and agriculture sector income on the regional economy in Lampung Province for the 2018-2022 period. The type of research used is quantitative research with the analysis technique used, namely multiple linear regression analysis using SPSS version 20. The results of the analysis show that the fisheries and agriculture sector has an effect on the regional economy. Therefore, all hypotheses in this study are accepted.